2012
DOI: 10.3390/s121013813
|View full text |Cite
|
Sign up to set email alerts
|

Two Proximal Skin Electrodes — A Respiration Rate Body Sensor

Abstract: We propose a new body sensor for extracting the respiration rate based on the amplitude changes in the body surface potential differences between two proximal body electrodes. The sensor could be designed as a plaster-like reusable unit that can be easily fixed onto the surface of the body. It could be equipped either with a sufficiently large memory for storing the measured data or with a low-power radio system that can transmit the measured data to a gateway for further processing. We explore the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…Beside the wearing comfort, which is achieved by reducing the number and length of the wires, these devices have very high reliability [1,2,3,4,5,6,7]. In human medicine supporting clinical validation data on wireless body electrodes grow [1,5,6,7,8,9,10,11,12], but in veterinary medicine this is to our knowledge the first report of the ECG data obtained in animals with a wireless body electrode attached to the skin and connected to a smart phone (tablet) via low power Bluetooth technology. The aim of these pilot measurements was to find out whether the limitations of the conventional Holter monitoring could be surmounted.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the wearing comfort, which is achieved by reducing the number and length of the wires, these devices have very high reliability [1,2,3,4,5,6,7]. In human medicine supporting clinical validation data on wireless body electrodes grow [1,5,6,7,8,9,10,11,12], but in veterinary medicine this is to our knowledge the first report of the ECG data obtained in animals with a wireless body electrode attached to the skin and connected to a smart phone (tablet) via low power Bluetooth technology. The aim of these pilot measurements was to find out whether the limitations of the conventional Holter monitoring could be surmounted.…”
Section: Introductionmentioning
confidence: 99%
“…heart rate determination, arrhythmia identification and characterization, ST segment denivelation, etc. For example, to determine the respiration rate, we found the best positions for the respiration body sensor [16] and proved that a single sensor of body surface potentials difference on proximal skin electrodes can be used for combined measurements of respiratory and cardiac activities (Fig.4).…”
Section: A Ecg Sensor Performance Resultsmentioning
confidence: 64%
“…As a successful case, we refer to the respiration rate extraction directly from WBBE [16]. We confirmed that several DLs on positions near the center of the chest provide adequate signals for ECG-derived respiration (EDR) algorithms that can reliably extract respiration rates from variations in the R-peak amplitudes.…”
Section: ) Extraction Of Hidden Information From Wbbementioning
confidence: 59%
See 1 more Smart Citation
“…The method presented can be applied retrospectively to ECG measurements in cases where breathing pattern is measured simultaneously or can be reconstructed from the ECG data [20]. The proposed methodology can be used in ambulatory environment to measure the vagal activity or to follow the level of functional re-innervation of transplanted hearts.…”
Section: Discussionmentioning
confidence: 99%